Cutting wages and employment in the public sector: Smarter fiscal consolidation strategies needed - Vera Glassner; Andrew Watt (Intereconomics, 2010)
This article provides an overview of the impact of public sector pay and employment cutbacks in EU countries and discusses their justifi cation as part of austerity packages. It begins with the outcomes in the countries first hit by the economic crisis before discussing the impact of the crisis and the perceived need for austerity on collective bargaining in the public sector of other EU countries. It then turns to the arguments put forward for focusing on public sector cuts as a means of fi scal consolidation and submits them to critical review. Policy conclusions are drawn regarding collective bargaining, public sector pay issues and pathways to fiscal consolidation in Europe that would be more effective in economic terms and more equitable in social terms.
Keywords: 330